Evaluasi Unsur Pengendalian Internal dalam Pengelolaan Dana Program Indonesia Pintar (PIP) pada SMPN 1 Maospati Kabupaten Magetan - Mulyaningrum, Fita; Pawestri, Hartini Prasetyaning; Zainudin, Zainudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to analyze and evaluate the elements of Government Internal Control (SPIP) according to PP No. 60 of 2008 in the management of PIP funds at SMPN 1 Maospati. The main informants in the study were 3 people and additional informants were 6 people. The research method used is descriptive qualitative with data collection methods from interviews with informants, observation and documentation. The results of this study indicate that the internal control elements of PIP fund management have been running well according to the regulations set by the government, but there are some inputs on control activities. In controlling activities, the school should hold HR coaching for PIP managers and make benchmarks to assess the performance of PIP managers so that PIP management in this school can run optimally.